Behind the Zone of Avoidance of the Milky Way: What Can We Restore by Direct and Indirect Methods? - Vavilova, I.B.; Elyiv, A.A.; Vasylenko, M.Yu. (Радиофизика и радиоастрономия, 2018)
Purpose: to present a brief overview of methods for restoring the large-scale structure of the Universe behind the Zone of Avoidance (ZoA) of the Milky Way; to propose a new “algorithm of darning the ZoA” and new approach based on the Generative adversarial network (GAN) to recover galaxy distribution in the ZoA using optical surveys as an additional platform for programming the artificial neural networks. Предмет и цель работы: представить краткий обзор методов, которые применяются для восстановления распределения крупномасштабных структур Вселенной за зоной избегания (ZoA) Млечного Пути; предложить новый “алгоритм штопки зоны избегания” и новый подход, основанный на Генерирующих состязательных сетях (GAN) для восстановления распределения галактик в ZoA с использованием оптических обзоров в качестве дополнительной платформы для программирования искусственных нейронных сетей. Предмет і мета роботи: подати короткий огляд методів, які застосовуються для відтворення розподілу великомасштабних структур Всесвіту за зоною уникнення (ZoA) Чумацького Шляху;запропонувати новий “алгоритм штопання зони уникнення” і новий підхід, що грунтується на генеруючій змагальній мережі (GAN) для відновлення розподілу галактик в ZoA з використанням оптичних оглядів у якості додаткової платформи для програмування штучних нейронних мереж.